Prefabricated housing subsidy analysis in China based on an evolutionary game model - Shen, Kaicheng; Li, Xiaodong; Cao, Xinying; Zhang, Zhihui (Journal of Civil Engineering and Management, 2021)
Prefabricated housing and cast-in-site housing are two alternatives for selection by developers and customers. The government, as the policy maker, creates incentive policies to encourage developers and customers to choose prefabricated housing. This paper aims to analyze the subsidy mechanism to theoretically confirm the subsidies’ scopes, amounts and end times through an evolutionary game model and simulation. In the game model, government subsidies affect the interactions between developers and customers in the decision-making process. The findings are as follows: 1) The developer housing subsidy can lower the housing price, while the customer housing subsidy can increase the price; 2) The government should first offer the developers a larger subsidy amount during the early development stage and then offer the customers a smaller subsidy amount later; 3) The government should determine the end time based on the proportion of developers and customers who choose prefabricated housing; 4) A higher prefabrication ratio may not always improve the development of prefabricated housing, and there is an optimal production scale that creates the best development situation. The empirical analysis shows that this model can help the government develop reasonable and optimal subsidy policies within the limit of budget to stimulate developers and customers.